Epigenetic Mechanisms Are Involved in Sex-Specific Trans-Generational Immune Priming in the Lepidopteran Model Host Manduca sexta - Gegner, Jasmin; Baudach, Arne; Mukherjee, Krishnendu; Halitschke, Rayko; Vogel, Heiko; Vilcinskas, Andreas (Frontiers in Physiology, 2019)
Parents invest in their offspring by transmitting acquired resistance against pathogens that only the parents have encountered, a phenomenon known as trans-generational immune priming (TGIP). Examples of TGIP are widespread in the animal kingdom. Female vertebrates achieve TGIP by passing antibodies to their offspring, but the mechanisms of sex-specific TGIP in invertebrates are unclear despite increasing evidence suggesting that both male-specific and female-specific TGIP occurs in insects. We used the tobacco hornworm (Manduca sexta) to investigate sex-specific TGIP in insects because it is a model host for the analysis of insect immunity and the complete genome sequence is available. We found that feeding larvae with non-pathogenic Escherichia coli or the entomopathogen Serratia entomophila triggered immune responses in the infected host associated with shifts in both DNA methylation and histone acetylation. Maternal TGIP was mediated by the translocation of bacterial structures from the gut lumen to the eggs, resulting in the microbe-specific transcriptional reprogramming of genes encoding immunity-related effector molecules and enzymes involved in the regulation of histone acetylation as well as DNA methylation in larvae of the F1 generation. The third-instar F1 larvae displayed sex-specific differences in the expression profiles of immunity-related genes and DNA methylation. We observed crosstalk between histone acetylation and DNA methylation associated with sex-specific immune responses in the F1 generation derived from parents exposed to a bacterial challenge.Multiple routes for TGIP seem to exist in M. sexta and – partially sex-specific – effects in the offspring depend on the microbial exposure history of their parents. Crucially, the entomopathogen S. entomophila appears to be capable of interfering with TGIP in the host.